Implementation of an autonomous star recognition algorithm using hardware-software co-processing approach - Dang, Le Dang Khoa (2019)
There are various types of Attitude Determination sensors such as sun sensors, magnetometer, RF beacon but only Star Trackers can achieve the accuracy to arc seconds. A Star Tracker is an embedded system mounted on a spacecraft comprised of an Image sensor and a Computer. It helps determine the attitude of the satellite based on an Autonomous Star Recognition Algorithm. The Star Sensor would take an image of stars at its current position, and then the star pattern recognition algorithms would extract features to construct a pattern from the images. This pattern then is compared with a prebuilt Star Pattern Database to return the Star Identity of a star in the Image. This star identity is an important part to determine the attitude of the satellite.